Analysis of Deixis in Song Lyric in “Plastic Heart” by Miley Cyrus - Dewi, Putu Eka Purnama; Ayomi, Putu Nur; Ariyaningsih, Ni Nyoman Deni (Journal of Language and Applied Linguistics, 2023)
The aim of this research is to analyze the types of deixis found in the song lyric “Plastic Heart” by Miley Cyrus from Plastic Heart Album. This research applied for descriptive qualitative method and supported by simple quantitative calculate the percentage of each type of deixis. The observation methods were employed in this research to collect the data. Based on the result can be concluded that three main types of deixis are found in the song lyric, there are 56 data found of person deixis with a percentage of 61%. Next, 31 data found of time deixis with percentage 34% and last there is 4 data found of place deixis with percentage 5%. The most dominant data found in the song lyric is person deixis which refers to the speaker or the singer itself in the song. This research is expected to provide an understanding of deixis and the context that is conveyed by the speaker.